Competition, markups, and gains from trade: A quantitative analysis of China between 1995 and 2004 - HSU, Wen-Tai (Institutional Knowledge at Singapore Management University, 2020)
This paper provides a quantitative analysis of gains from trade in a model with head-to-head competition using Chinese firm-level data from Economic Censuses in 1995 and 2004. We find a significant reduction in trade cost during this period, and total gains from such improved openness during this period is 7.1%. The gains are decomposed into a Ricardian component and two pro-competitive ones. The pro-competitive effects account for 20% of the total gains. Moreover, the total gains from trade are 13 − 31% larger than what would result from the formula provided by ACR (Arkolakis et al., 2012), which nests a class of important trade models, but without pro-competitive effects. We find that head-to-head competition is the key reason behind the larger gains, as trade flows do not reflect all of the effects via markups in an event of trade liberalization.